STUDI KASUS PERBANDINGAN KINERJA KEUANGAN BANK CENTRAL ASIA TBK DAN BANK CENTRAL ASIA SYARIAH TBK PADA MASA PANDEMI COVID-19 DI INDONESIA - Ana Dwi Pertiwi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2021)
The Covid-19 pandemic that has spread has finally brought serious risks to the world economy, including Indonesia. In the midst of the Covid-19 pandemic, the total assets of Bank Central Asia Tbk and Bank Central Asia Syariah Tbk are still experiencing increasing growth. This study aims to compare the financial performance of Bank Central Asia Tbk and Bank Central Asia Syariah Tbk during the Covid-19 pandemic by using the ratio of Non Performing Loan (NPL) / Non performing financing (NPF), Loan to Deposit Ratio / Financing to Deposit Ratio ( FDR), Return On Assets, Operating Costs and Operating Income (BOPO) and Capital Adequacy Ratio. The data used in this study are the quarterly reports of Bank Central Asia Tbk and Bank Central Asia Syariah Tbk in the period March 2020 to September 2021. The method in this study is a comparative method which aims to compare the financial performance of Bank Central Asia Tbk and Bank Central Asia. Syariah Tbk during the Covid-19 pandemic. The results of this study indicate that there are significant differences in the financial performance of Bank Central Asia Tbk and Bank Central Asia Syariah Tbk during the Covid-19 Pandemic in all the ratios tested.